Newletter September (Medical Journals Sweden, 2021)
Is missing (News Letter)   HIGHLIGHTS Editor choice Physical inactivity after stroke Sara Botö, Dongni Buvarp, Per-Olof Hansson, Katharina S. Sunnerhagen, Carina U. Persson   Further highlights of this month in JRM: Cognition, confidence and power wheelchair use Alice Pellichero, Krista Best, Jean Leblond, Pauline Coignard, Éric Sorita, François Routhier   Fatigue and return to work after stroke Anna Norlander, Ingrid Lindgren, Hélène Pessah-Rasmussen, Gunvor Gard, Christina Brogårdh   Adaptations to rehabilitation services during the COVID-19 pandemic Luz H. Lugo-Agudelo, Kelly Mariana Cruz Sarmiento, Maria Alejandra Spir Brunal, Juan Velásquez Correa, Ana Maria Posada Borrero, Luisa Fernanda Mesa Franco, Rosarita Di Dio Castagna Ianini, Paola Andrea Ramírez Pérez LIS, Claudia Marcela Vélez, Daniel F. Patiño Lugo, Christoph Gutenbrunner